APOBEC3G-Mediated G-to-A Hypermutation of the HIV-1 Genome: The Missing Link in Antiviral Molecular Mechanisms - Okada, Ayaka; Iwatani, Yasumasa (Frontiers in Microbiology, 2016)
APOBEC3G (A3G) is a member of the cellular polynucleotide cytidine deaminases, which catalyze the deamination of cytosine (dC) to uracil (dU) in single-stranded DNA. These enzymes potently inhibit the replication of a variety of retroviruses and retrotransposons, including HIV-1. A3G is incorporated into vif-deficient HIV-1 virions and targets viral reverse transcripts, particularly minus-stranded DNA products, in newly infected cells. It is well established that the enzymatic activity of A3G is closely correlated with the potential to greatly inhibit HIV-1 replication in the absence of Vif. However, the details of the underlying molecular mechanisms are not fully understood. One potential mechanism of A3G antiviral activity is that the A3G-dependent deamination may trigger degradation of the dU-containing reverse transcripts by cellular uracil DNA glycosylases (UDGs). More recently, another mechanism has been suggested, in which the virion-incorporated A3G generates lethal levels of the G-to-A hypermutation in the viral DNA genome, thus potentially driving the viruses into "error catastrophe" mode. In this mini review article, we summarize the deaminase-dependent and deaminase-independent molecular mechanisms of A3G and discuss how A3G-mediated deamination is linked to antiviral mechanisms.